The Microbiology of Acute Exacerbations in Chronic Rhinosinusitis - A Systematic Review - Okifo, Oghenefejiro; Ray, Amrita; Gudis, David A. (Frontiers in Cellular and Infection Microbiology, 2022)
Background Acute exacerbations (AE) in chronic rhinosinusitis (CRS) are a common and important clinical issue. However, relatively little is known regarding the underlying microbiology that drives exacerbations or how it relates to the microbiome of CRS. The purpose of this study is to examine the literature to characterize the microbiome associated with acute exacerbations in a chronic rhinosinusitis setting. Understanding this disease process may facilitate targeted antibiotic therapy, reduced antibiotic resistance, and offer more effective disease control and treatment efficacy. Objective To characterize the microbiome associated with acute exacerbations of chronic rhinosinusitis (AECRS). Methods We conducted a systematic review of the literature on Medline, Embase, and Web of Science databases from January 1990-June 2021 to identify studies related to AE in CRS. Exclusion criteria include non-English, non-human studies, and case reports. Studies without culture or PCR data were also excluded. Results Fourteen studies were identified which provided detailed data regarding sinus microbiome in AECRS patients. In these patients, a total of 1252 individual isolates were identified. While common acute pathogens were identified in high frequencies in the sinonasal cultures (Staphylococcus pneumonia, Haemophilus influenza), the predominant bacteria were Staphylococcus aureus (including methicillin-sensitive Staphylococcus aureus) and Pseudomonas aeruginosa. Patient characteristics that may represent higher risk phenotypes were not consistently collected in the studies. Discussion of antimicrobial sensitivities and/or resistance were included in 7/14 studies. Conclusions This systematic review identifies the predominant microbiology species that may contribute to AECRS. Further studies are needed to understand the pathogenic role of bacteria and viruses in AECRS and to identify associated comorbidities and patient phenotypes that may predispose to AE. The optimal treatment regimen for AECRS remains unclear.